EXPLORING THE LINK BETWEEN ROMANIAN ACCOUNTING STUDENTS’ GOAL ORIENTATIONS, SELF-EFFICACY, TEST ANXIETY AND PERFORMANCE: A CLUSTER ANALYSIS APPROACH - MÜLLER, Camelia-Ancuța (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
This empirical study examines the relationship between learning motivation, self-efficacy, test anxiety, and academic performance in the context of a Financial Accounting course, using Achievement Goal Theory (AGT) as a framework. A sample of 149 second-year students enrolled in the Accounting and Management Information Systems program completed a questionnaire based on the Motivated Strategies for Learning Questionnaire (MSLQ). The data were analyzed using correlation, cluster analysis, and ANCOVA. The results confirmed significant differences between four motivational profiles: mastery, performance, multiple goals, and low motivation, regarding their impact on self-efficacy, test anxiety, and performance. The findings suggest that students with multiple goals achieve better academic outcomes, emphasizing the importance of a multidimensional approach to learning motivation. JEL classification: A22, I23, M41.